Pengaruh Model Pembelajaran Creative Problem Solving (CPS) Terhadap Pemahaman Konsep Peserta Didik pada Pembelajaran Fisika di SMA Negeri 1 Ampek Angkek - Khairunnisa, Khairunnisa; Yurnetti, Yurnetti; Hidayati, Hidayati; Emiliannur, Emiliannur (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the influence of the creative problem solving (CPS) learning model on students' understanding of physics concepts in physics learning in class XI phase F at SMA N 1 Ampek Angkek. This study utilizes a quantitative approach with the type of Quasi Experiment Design. The research instrument is in the form of multiple-choice questions with five possible answers. Before the test is given, the instrument will be tested for validity, reliability, difficulty level and differentiation first. A total of 72 physics students of eleventh grade phase F participated in this study; 32 from the experimental group and 36 from the control group. The data analysis techniques used are normality tests, homogeneity, and mean difference tests. The findings of the study show that the application of the CPS learning model affects students' understanding of concepts. Both groups of students who use the direct learning model and those who use the CPS model have a significance value of <0.05 in the statistical analysis carried out using the t-test.